The Application of Disciplinary Values in Improving Character in the Learning Process of Pancasila and Citizenship Education at SMPN 2 Padang - Violina, Suci; Jaenam, Jaenam; Asril, Asril (Jurnal Pendidikan Amartha, 2022)
This research was motivated by several problems, including: SMPN 2 Padang has an A accreditation and is one of the favorite schools but because student admissions under the zoning system have an impact on student behavior because tests are not applied when new students are admitted to school, problems related to student discipline are found. . An example is being late for school and there are students who do not do their homework when the learning process takes place. The purpose of this study was to describe the form of applying the value of discipline at the time of the implementation of activities to open learning to improve the character of students at SMPN 2 Padang. To describe the form of application of disciplinary values during the implementation of core learning activities towards improving the character of students at SMPN 2 Padang. To describe the form of application of the value of discipline at the time of the closing of the learning activities towards improving the character of students at SMPN 2 Padang. The research method used is qualitative with descriptive research which produces descriptive data in the form of written or spoken words from people and observed behavior at the research location of SMP N 2 Padang. With data collection techniques through Observation, Interview by seeking complete and in-depth information and Documentation Study. The results of this study indicate that first, the form of applying the value of discipline in the learning process of activities opens to improving the character of students at SMP Negeri 2 Padang, namely in this activity the teacher applies the value of discipline by coming to class on time, discipline in class cleanliness, delivering grades. -discipline values to students, explain the rules of the learning process as a form of applying discipline and also explain sanctions or penalties if students violate. Second, the form of applying the value of discipline in the learning process of core activities to improving the character of students at SMP Negeri 2 Padang, namely in this activity carried out by the teacher to shape the character of students by linking the material with the value of discipline, being consistent with the rules made, being able to behave assertive, giving praise to students if they can answer questions. Third, the form of applying the value of discipline in the learning process of closing activities to improving the character of students at SMP Negeri 2 Padang, namely before ending the learning activities, the teacher asks students to discuss things that have been learned, asking for the attitude of responsibility of students who are picket also including in applying discipline and closing learning activities by praying and giving greetings.